2017
DOI: 10.3389/fphar.2017.00143
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Successfully Inhibited the Computationally Identified CYP2A6 Enzyme-Mediated Bioactivation of Aflatoxin B1 in Arbor Acres broiler

Abstract: Cytochrome P450 enzymes are often responsible for the toxic and carcinogenic effects of toxicants, such as aflatoxin B1 (AFB1). The human hepatic CYP2A6 enzyme mediates the oxidative metabolism of several procarcinogens. In this study, we characterized a partial sequence of CYP2A6 gene from Arbor Acres (AA) broiler and studied its role in AFB1 bioactivation. Moreover, the effect of curcumin on CYP2A6 is illustrated. Six groups of AA broiler were treated for 28 days including the control group (fed only basal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…In addition, some people are more susceptible to getting mycotoxicosis than others, and this is due to the pharmacogenetic variability where specific gene mutations such as cytochrome p450 (CYP 450) genes could either increase or decrease the metabolic activity (cytotoxicity) of the challenging mycotoxins (Sun et al, 2016 ). For instance, in both in vivo (Muhammad et al, 2017 ) and in vitro (Lewis et al, 2000 ) studies, CYPs' 1A2 and 3A4 appear as the most important enzymes that increased metabolism of AFB1 to its active form, AFB1-8,9-epoxide and subsequently to AFB1-DNA adduct formation, in which the biomarker has been linked to the development of liver cancer (Ceccaroli et al, 2015 ).…”
Section: Importance Of Research On Mycotoxinmentioning
confidence: 99%
“…In addition, some people are more susceptible to getting mycotoxicosis than others, and this is due to the pharmacogenetic variability where specific gene mutations such as cytochrome p450 (CYP 450) genes could either increase or decrease the metabolic activity (cytotoxicity) of the challenging mycotoxins (Sun et al, 2016 ). For instance, in both in vivo (Muhammad et al, 2017 ) and in vitro (Lewis et al, 2000 ) studies, CYPs' 1A2 and 3A4 appear as the most important enzymes that increased metabolism of AFB1 to its active form, AFB1-8,9-epoxide and subsequently to AFB1-DNA adduct formation, in which the biomarker has been linked to the development of liver cancer (Ceccaroli et al, 2015 ).…”
Section: Importance Of Research On Mycotoxinmentioning
confidence: 99%
“…Further confirmatory experiments will clearly form a link between curcumin and the CYP450 isoenzymes which could prove effective establishing curcumin as an anti-AFB1 feed additive. Recently, Mohammad et al [ 121 ] have reported new insight into in vivo activation of AFB1 in broilers by the CYP2A6 enzyme. They have reported a dose-dependent hepatoprotection and CYP2A6 activity inhibition.…”
Section: Curcumin-mediated Afb1 Toxicity Control and Protective Mementioning
confidence: 99%
“…Aflatoxin B1 (AFB1) is the most common in feed and believed to be the most biologically active form causing cytotoxicity, genotoxicity and oxidative stress (Sweeney and Dobson, 1998); (Vaamonde et al, 2003) and (El-Nekeety et al, 2017). AFB1could be activated by cytochrome P450 (CYP450) into a highly reactive metabolite that reacts with DNA and proteins inducing genotoxicity and cytotoxicity (Cervino et al, 2007) and (Muhammad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%